A recurrent case of pyruvate dehydrogenase complex deficiency - Venkatesan, Dhivya; Samal, Sunil Kumar; Vishalakshi, Ashwini; P., Pallavee; S., Prabhu C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Pyruvate dehydrogenase complex deficiency is an inherited inborn error of metabolism causing lactic acidosis and several neurological symptoms. Its incidence and prevalence are not known. Here we report about a child with global developmental delay, central hypotonia and dyskinesia. Sanger sequencing was done and found to have homozygous nonsense mutation in exon 4 of PDHX gene causing lactic acidosis. In the next pregnancy selective Sanger variant analysis was carried out and the fetus was also found to be affected with the same genetic defect. Hence medical termination of Pregnancy was carried out. We conclude that early selective genetic testing will prevent further affected births.